FEATURES OF LONG-TERM MENTAL DISORDERS IN THE VICTIMS OF CHERNOBYL ACCIDENT - Rymsha, S.V.; Ratsyborynska-Polyakova, N.V.; Gavrylyuk, A.O. (World of Medicine and Biology, 2020)
The purpose of the work was to study the features of the clinical structure, the pathopsychological and pathophysiological mechanisms of mental disorders formation in the victims of the Chornobyl accident in the long term. The study of the mental status in the liquidators - ІІІ groups of complex survey - 202 persons – liquidators of the Chernobyl disaster, that worked in 1988 in 30 – kilometer zone, the radiation level ranged from 0.2 to 25 Gy - took into account the system of risk factors, which included social, radiological, medical aspects, social factors including hypokinesia, unsustainable diet, smoking, alcohol consumption and radiological factors. In the affected by the Chernobyl accident in 1986 long-term consequences for mental health were revealed, mental disorders were found to be dependent on the dose and the relationship between the severity of lesions and radiation symptoms. The study of the liquidators’ health can extend the understanding of the relationship between PTSD, depression, risk of internal diseases and recovery. According to our data, the central element in the structure of psychopathological manifestations is psycho-vegetative syndrome with affective accompaniment. Thus, the conclusion was made that psychosocial effects of stress as a result of Chernobyl disaster shows how important it is to continue monitoring of the mental health in the population to establish the relationship between mental well-being, physical illness and mortality.